Hubungan Kecerdasan Emosional dengan Resiliensi pada Mahasiswa yang Sedang Menyusun Skripsi - Sitti Anggraini; Agustinus Rudi Yanto (Departement of Mathematics Education, 2023)
Resilience has an important role for students who are preparing or completing a thesis. Students who have the ability to control behavior, emotions, and attention in dealing with problems are usually known as resilient students. This research is a correlational study that aims to determine whether there is a correlation between emotional intelligence and the resilience of students who are preparing their thesis. The subjects used in this study were 46 students of the Faculty of Social Sciences, University of Nusa Nipa. The results obtained show that there is a positive and significant relationship between emotional intelligence and resilience, with a relationship efficiency of 0.352 and a significance level of 0.016 (p <0.05. also conversely the lower the emotional intelligence, the lower the resilience of students who are preparing a thesis.